Back Cover: Large‐Scale Synthesis of Helicene‐Like Molecules for the Design of Enantiopure Thin Films with Strong Chiroptical Activity (Chem. Eur. J. 10/2016). Issue 10 (27th January 2016) - Bensalah‐Ledoux, Amina; Pitrat, Delphine; Reynaldo, Thibault; Srebro‐Hooper, Monika; Moore, Barry; Autschbach, Jochen; Crassous, Jeanne; Guy, Stéphan; Guy, Laure
Abstract : The fabrication and chiroptical properties of organic thin films made from helicene‐like molecules have been described. The cover illustration represents an isotropic molecular thin film deposited on a glass substrate. It is penetrated by a linearly polarized light, which rotates due to high chirality of the material. Moreover, this thin film is reflected on water, making a symbolic mirror image of a pair of enantiomers. More information can be found in the Full Paper by M. Srebro‐Hooper, J. Crassous, L. Guy, et al. onpage 3333 ff.